The impact of digital transformation on financial inclusion: Evidence from MSMEs in Indonesia - Harunurrasyid, Harunurrasyid; Gustriani, Gustriani; Mardalena, Mardalena; Nida, Rahma (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
The integration of digitalization in micro, small, and medium enterprises (MSMEs) has become a cornerstone in enabling these businesses to thrive within an increasingly competitive and dynamic marketplace. This study, based on data from a survey of 5,553 MSMEs, examines the impact of digitalization on financial inclusion and enterprise productivity. The findings reveal that digitalization reduces MSMEs' dependence on traditional banking systems for credit, facilitating access to alternative financing options through internet-based technologies. Moreover, advancements in technology contribute to increased bank loans and improved MSME productivity by overcoming conventional barriers to financial inclusion and reaching previously underserved segments of the MSME sector. The adoption of formal business status fosters structured and organized operations, thereby enhancing overall performance, while the mere longevity of a business does not guarantee increased productivity. Additionally, improved financial management skills acquired through training are shown to diminish reliance on traditional bank financing. The study also highlights the adverse effects of the COVID-19 pandemic, including lockdown measures, supply chain disruptions, and changes in consumer behavior, which collectively led to a decline in MSME productivity.